Effects of early postnatal hyperoxia exposure combined with early ovalbumin sensitization on lung inflammation and bacterial flora in a juvenile mouse model of asthma - Li, Jingyan; Bao, Tianping; Cao, Linxia; Ma, Mengmeng; Zhang, Yuan; Tian, Zhaofang (Frontiers in Microbiology, 2023)
The aim of this study is to explore the effects of early postnatal hyperoxia exposure combined with early ovalbumin (OVA) sensitization on lung inflammation and bacterial flora in neonatal mice on a juvenile mouse model of asthma.Methods: Thirty-two newborn female C57BL/6J mice were randomly divided into four groups, which including room air+phosphate-buffered saline (PBS) group, hyperoxia+PBS group,room air+OVA group, and hyperoxia+OVA group, according to the hyperoxia exposure and/or OVA induction. Mice were exposed to either 95% O2 or room air for 7 days after birth; after 7 days, they were exposed to air and received an intraperitoneal injection of OVA suspension or PBS solution on postnatal days 21 (P21) and 28 (P28). From P36 to P42, the mice were allowed to inhale of 1% OVA or 0.9% NaCl solution. The mice were observed after the last excitation. HE staining was performed to observe the pathological changes in lung tissues. Wright-Giemsa staining was used to perform bronchoalveolar lavage fluid (BALF) leukocyte sorting.Enzyme-linked immunosorbent assay was used to determined the cytokines levels of interleukin (IL)-2, IL-5, IL-13, IL-17A, and IL-10 and serum IgE levels in BALF.Additionally, 16S rRNA sequencing was used to analyze the characteristics of lung microbiota.Results: Mice in the hyperoxia+OVA group showed asthma-like symptoms. HE staining results revealed a significant thickening of the airway wall and airway inflammation. BALF analysis of cellular components showed significant increases in total leukocyte and eosinophil counts and the levels of cytokines related to Th2 (IL-5 and IL-13) and Th17 (IL-17A); 16S rRNA sequencing revealed that the main members of the pulmonary microflora were Actinobacteriota, Proteobacteria, Firmicutes, and Bacteroidota at the phylum level. In addition,the bacteria with a major role were Acinetobacter and Moraxellaceae in the O2 + OVA group.The mouse suffering from postnatal hyperoxia exposure and early OVA sensitization, changes in symptoms, pathology, leukocyte and eosinophil counts, and levels of different T-cell cytokines in BALF and lung microbiota, which may provide a basis for the establishment of a juvenile mouse model of asthma.